Analysis of Mercury Concentration on The Water and Sediment at Tiabo River, Roko, West Galela District, North Halmahera - Margaretha Tabita Tuny; Kurnia Kurnia (Chemistry Department, The University of Brawijaya, 2020)
Gold mining activity at Tiabo river in the North Halmahera causes the water on the river is contaminated by mercury. The contamination mercury on the water can damage food chain and adverse consequences toward health of people, fish, and so on. The purpose of this study is to obtain the concentration of mercury contamination that was caused by gold mining activity. The water and sediment sample was obtained by purposive sampling. The characterization of concentration mercury in the water and sediment using mercury analyzer HG-300 in the wave length 253.72 nm. The result shows that mercury concentration of the water in the six and five sample point in the rainy session and the dry session respectively is <0.66 µg/L, and the mercury concentration in the sediment shows that the lower value in the upstream river was 1.2 mg/kg and the higher concentration in the middle of river was 8.94 mg/kg respectively in the rainy session. The result indicates that the contamination mercury in the moderate danger level according to the IADC/CEDA data standard.